Implementation of Syibhul Iddah in KUA Klojen District: A Study Based on the Circular Letter of the Ministry of Religious Affairs - Putri, Ramadhani Islam; Suhadak, Faridatus (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Iddah is a waiting period given to women to check whether they are pregnant or not. Until the issuance of the Circular Letter from the Director General of Islamic Community Guidance, Ministry of Religious Affairs No: P-005/DJ.III/Hk.00.7/10/2021, which regulates the application of the waiting period (Syibhul Iddah) for men who have divorced before remarrying. This research aims to describe the implementation of Syibhul Iddah based on the Circular Letter at the KUA Klojen District and to analyze its concept from the perspective of Wahbah Az-Zuhaili. This research uses a juridical-empirical approach with a qualitative descriptive method. Data sources were obtained from primary sources in the form of interviews with informants such as the Head of KUA, modin, and widowed prospective grooms, and were supported by secondary sources such as relevant literature, including the Islamic book